2017
DOI: 10.1109/tnsre.2017.2659749
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Dynamic Joint Stiffness from Multiple Short Data Segments

Abstract: This paper presents our new method, Short Segment-Structural Decomposition SubSpace (SS-SDSS), for the estimation of dynamic joint stiffness from short data segments. The main application is for data sets that are only piecewise stationary. Our approach is to: 1) derive a data-driven, mathematical model for dynamic stiffness for short data segments; 2) bin the non-stationary data into a number of short, stationary data segments; and 3) estimate the model parameters from subsets of segments with the same proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…However, the algorithm could be modified to work with non-periodic data; this would require estimating the initial conditions of each trial in the ensemble as part of the identification problem as done in Jalaleddini et al (2017). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the algorithm could be modified to work with non-periodic data; this would require estimating the initial conditions of each trial in the ensemble as part of the identification problem as done in Jalaleddini et al (2017). …”
Section: Discussionmentioning
confidence: 99%
“…Under TV conditions, a TV version of the parallel-cascade structure, shown in Figure 1, has been successfully applied to describe the overall dynamic joint stiffness (Giesbrecht et al, 2006; Ludvig et al, 2011; Guarin and Kearney, 2012, 2015b; Jalaleddini et al, 2017). However, the identification algorithms used to estimated the TV model parameters require very large data sets and so are difficult to use in practice.…”
Section: Model Formulation and Parameter Identificationmentioning
confidence: 99%
“…Any errors in estimating the SV will result in identification performance to be lower than that predicted from the simulations. (ii) Identification model structure: We made two assumptions about the model structure: (1) Stiffness dynamics at the ankle can be represented using a PC model structure ; this model has been widely used and shown to be successful in predicting the stiffness torque for both quasi-stationary and TV conditions (Mirbagheri et al, 2000; Sobhani Tehrani et al, 2014; Jalaleddini et al, 2017), (2) The reflex pathway has a delay of 40–45ms; this is shown to be true in many studies (Stein and Kearney, 1995; Kearney et al, 1997; Mirbagheri et al, 2000). There were few assumptions about structures of the elements of the PC model.…”
Section: Discussionmentioning
confidence: 99%
“…Short segment methods (Ludvig and Perreault, 2012; Rouse et al, 2014; Jalaleddini et al, 2017) divide non-stationary data into a number of segments with quasi-stationary behavior and identify a time-invariant model for each segment. The segmentation is not always trivial and often requires the TV behavior to be very slow.…”
Section: Introductionmentioning
confidence: 99%
“…However, the identification algorithms used in those studies require large amounts of data, making them difficult to apply under certain practical conditions. [22], [23]; or make the strong assumption that there is a static-nonlinear relation between the model parameters and joint position or torque [24].…”
mentioning
confidence: 99%